EVOLVED MARE BASALT MAGMATISM, HIGH MG/FE FELDSPATHIC CRUST, CHONDRITIC IMPACTORS, AND THE PETROGENESIS OF ANTARCTIC LUNAR BRECCIA METEORITES METEORITE HILLS 01210 AND PECORA ESCARPMENT 02007 - Day J.M.D.; Floss C.; Taylor L.A.; Anand M.; Patchen A.D. (My University, 2006)
Antarctic lunar meteorites Meteorite Hills 01210 and Pecora Escarpment 02007 are breccias that come from different regolith lithologies on the Moon. MET 01210 is composed predominantly of fractionated low-Ti basaltic material and is classified as an immature, predominantly basaltic glassy matrix regolith breccia. PCA 02007 is a predominantly feldspathic regolith breccia consisting of metamorphosed feldspathic, noritic, troctolitic and noritic-anorthosite clasts, agglutinate and impact-glasses, as well as a number of basaltic clasts with mare and possible non-mare affinities. The basalt clasts in MET 01210 have undergone ’Fenner’ trend enrichments in iron and may also have witnessed late-stage crystallization of zircon or a zirconium-rich mineral. Some of the features of MET 01210 are similar to other basaltic lunar breccia meteorites (e.g., Northwest Africa 773; Elephant Moraine 87521/96008; Yamato 793274/981031), but it is not paired with them. The presence of metamorphic anorthositic clasts as well as agglutinates indicates a small regolith component. Similarities with previously discovered evolved (e.g., LaPaz Icefield 02205; Northwest Africa 032) and ferroan (e.g., Asuka 881757; Yamato 793169) basaltic lunar meteorites suggest a similar mare source region for MET 01210. Despite lack of evidence for pairing, PCA 02007 shares many features with other feldspathic regolith breccias (e.g., Yamato 791197, Queen Alexandra Range 94281), including a high Mg/Fe whole-rock composition, glass spherules, agglutinate fragments and a diverse clast inventory spanning the range of ferroan anorthosite and high magnesium suite rocks. Some of the basalt fragments in this sample are fractionated and have an igneous origin. However, the majority of the basalt fragments are impact melt clasts. PCA 02007 supports previous studies of feldspathic lunar meteorites that have suggested an aluminous crust for the Moon, with compositions more similar to magnesium granulite breccias than ferroan anorthosites. A ’chondrule-like’ fragment found in PCA 02007 and unlike any previously described lunar material is described and tentatively identified as the remnants of a chondritic lunar impactor. This clast is porphyritic with equant olivines that have forsterite-rich cores (Fo>98), extreme normal zonation to more fayalitic rims (Fo>44), and a mineral assemblage with rare earth element abundances distinct from described lunar material and more similar to chondrules found in ordinary or carbonaceous chondrites. Its discovery and description is significant for understanding the composition of lunar impactors. Previously, the main evidence for chondritic lunar impactors was from chondritic relative abundances and near chondritic ratios of highly siderophile elements in lunar impact melt breccias. However, the presence of this clast, along with two other chondritic clasts from Apollo soils 12037 and 15602, provides clues to the identity of ancient meteorite impactors on the Moon. ? 2006 Elsevier Inc. All rights reserved.
Keywords: BRECCIA; LUNAR METEORITE; MARE BASALT; PETROGENESIS; REGOLITH; PECORA; SPHERULES